Speech, Language and Swallowing Disorders in the Symptomatology of Post-COVID-19 Syndrome - Simona Hlaváčová (Listy klinicke logopedie)
COVID-19 is a highly contagious disease caused by the SARS-CoV-2 coronavirus, and its pandemic has gradually affected the entire world. While most symptoms of this disease disappear during the acute phase, some symptoms may persist for several months. This condition is referred to as the post-COVID-19 syndrome. Cognitive impairment is one of the possible long-lasting symptoms that are directly related to patients' communication abilities. These difficulties manifest mainly in the area of verbal recall, verbal fluency and the informational value of discourse. This review summarises the existing information on cognitive-communication disorders associated with the post-COVID-19 syndrome, but also provides an overview of other long-term persistent complications of language, speech and swallowing that may arise from COVID-19.